MODEL PENYUSUNAN PENDIDIKAN AGAMA ISLAM BERDASARKAN PROPORSI TINGKAT KESUKARAN - Nila Wahyuni Nasution; Saiful Salim Marbun; Sahat Parulian; Syafnan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of a proper assessment instrument is an essential factor in measuring the achievement of learning objectives in Islamic Religious Education (IRE). A high-quality test instrument should be designed based on a clear test blueprint, measurable indicators, and an appropriate level of item difficulty to comprehensively assess students’ abilities. This article aims to describe a model for developing test blueprints, learning indicators, and test items in Islamic Religious Education based on a proportional distribution of item difficulty levels. The method employed is a library research approach through the examination of various literature related to educational evaluation, test instrument development, and learning assessment in Islamic education. The findings indicate that the preparation of a test blueprint should align with learning outcomes, competencies to be measured, subject matter, indicators, item formats, and the number of questions. The development of indicators is based on the competencies to be achieved, serving as guidelines for constructing test items. Furthermore, test items are developed by considering a proportional distribution of difficulty levels, consisting of 20% easy items, 60% moderate items, and 20% difficult items. This distribution enables the test instrument to possess good discriminating power and effectively measure students’ abilities across different proficiency levels. Therefore, a systematic model for developing test blueprints, indicators, and test items can enhance the validity and reliability of assessment instruments in Islamic Religious Education learning.